Advances in flexible hydrogels for light-thermal-electricity energy conversion and storage. (April 2023) - Kong, Lingshuang; Yuan, Zhiang; Sun, Nianhua; Ding, Junjie; Liu, Sen; Zhang, Shaohua; Lv, Zhiqiang; Xu, Wenlong; Liu, Guijing; Liu, Xiguang
Abstract: In order to improve energy efficiency and reduce energy waste, efficient energy conversion and storage are current research hotspots. Light-thermal-electricity energy systems can reconcile the limited supply of fossil fuel power generation with the use of renewable and clean energy, contributing to green and sustainable production and living. Flexible hydrogels have been widely investigated in light-thermal-electricity systems because of their porous network structure, large specific surface area, high water content, and low thermal conductivity (0.3–0.39 W/m/K), which can efficiently perform charge transfer and provide more reaction sites for effective or assisted energy conversion efficiency. Flexible hydrogels have been used as electrolytes or electrodes in light-thermal-electricity energy systems for energy conversion processes, which effectively reduce the risk of liquid electrolyte volatilization and leakage, and also improve the flexibility of energy devices, providing a good strategy for wearable devices. In this paper, we focus on the energy conversion and storage mechanism of flexible hydrogels in light-thermal-electricity energy conversion systems. We also introduce the current status of flexible hydrogels in various energy systems from the perspective of energy conversion and analyze the role and advantages of flexible hydrogels. Finally, we propose a proposal for flexible hydrogel research in light-thermal-electricity conversion systems and hope to inspire readers with design ideas. Highlights: The advantages of flexible hydrogels materials are systematically summarized. The applications of flexible hydrogels are analyzed from the perspective of energy conversion. The current problems of flexible hydrogels are pointed out and solutions are proposed.